2013
DOI: 10.1108/he-07-2012-0041
|View full text |Cite
|
Sign up to set email alerts
|

Moderating teen drinking: combining social marketing and education

Abstract: Acknowledgments 2The authors wish to acknowledge the financial support provided by Queensland Catholic Education Commission and Griffith University and the support of the students, parents, teachers and support staff employed at the schools. Without your support this study would not have been possible. We also wish to thank the anonymous reviewers of our earlier manuscript for their time and valuable insight. Finally, we wish to personally thank Mr. John Percy for his advice and guidance throughout the project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 34 publications
0
65
0
1
Order By: Relevance
“…The descriptive norms items were adopted from Rhodes and Courneya (2003a), and the injunctive norms items were adapted from Perugini and Conner (2000). Both affective and instrumental attitudes scales were adapted from Norman and Conner (2006), and the behavioural intention scale items were adapted from Rundle-Thiele, Russell-Bennett, Leo, and Dietrich (2013). The PBC scales were adapted from Rhodes and Courneya (2003a).…”
Section: Methodsmentioning
confidence: 99%
“…The descriptive norms items were adopted from Rhodes and Courneya (2003a), and the injunctive norms items were adapted from Perugini and Conner (2000). Both affective and instrumental attitudes scales were adapted from Norman and Conner (2006), and the behavioural intention scale items were adapted from Rundle-Thiele, Russell-Bennett, Leo, and Dietrich (2013). The PBC scales were adapted from Rhodes and Courneya (2003a).…”
Section: Methodsmentioning
confidence: 99%
“…One of the main social issues today is excessive alcohol consumption (Kubacki, Siemieniako, & Rundle‐Thiele, ). Research has shown that alcohol use is a significant risk factor for various health problems (Gordon, MacKintosh, & Moodie, ; Greenfield, Midanik, & Rogers, ; Hao, Chen, & Su, ; Thompson et al, ; Deshpande & Rundle‐Thiele, ; Rundle‐Thiele, Russell‐Bennett, Leo, & Dietrich, ). Because of the inherent differences in historical drinking cultures, as well as differences in alcohol policy globally (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Rundle-Thiele, 2011; Rundle-Thiele, Russell-Bennett, Leo, & Dietrich, 2013). Because of the inherent differences in historical drinking cultures, as well as differences in alcohol policy globally (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite success in allied health behavior change areas, social marketing has received limited attention in alcohol education programs in school settings. The effectiveness of social marketing's application in an alcohol program in a school setting has been documented by Rundle‐Thiele et al Despite success in allied health behavior change areas, social marketing has received only limited attention in the context of alcohol interventions delivered in school settings.…”
mentioning
confidence: 99%